PENGGUNAAN STORYTELLING TECHNIQUES DALAM PEMBELAJARAN BAHASA INGGRIS SISWA KELAS VIII SMPN 6 LANGKE REMBONG - Nggiring Junior, Oswaldus Teten; Remild, Emerensiana; Daar, Gabriel Fredi (CV. Alina, 2025)
This community service (PkM) activity was carried out at SMPN 6 Langke Rembong, Manggarai Regency, East Nusa Tenggara, with a focus on the application of storytelling techniques to improve the English speaking skills of grade VIII students. This activity was designed as a response to the low self-confidence and involvement of students in speaking English in class. A total of 21 students were involved in this program which lasted for three learning sessions. Various methods were used, such as interactive presentations, storytelling practice, language games, small group discussions, and joint reflection. Storytelling was chosen because it was able to present a pleasant learning atmosphere, bring language closer to students' experiences, and foster their courage to appear and speak. The results of the activity showed that students were more confident, active in using new vocabulary, and enjoyed the learning process as a whole. In addition, this activity also showed that learning strategies that touch on students' affective aspects can have a significant impact on improving their language skills.